Distribusi Pendapatan Dan Kemiskinan Rumah Tangga Petani Di Wilayah Pasang Surut (Kasus Di Desa Saleh Mukti Kecamatan Air Salek Kabupaten Banyuasin Sumatera Selatan) - Yanter Hutapea; Budi Raharjo (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Hutapea, et al. Income Distribution and Farmer Household Poverty in Tidal Swamp Region (Case In Saleh Mukti Village, Air Salek Sub-District, Banyuasin Regencies, Southsumatra). JLSO 5(2):159-169. The existence of farmers in tidal swamp transmigration areas have changed compare to the initial conditions, seen in tenure, farm business management and livelihoods,that’s impact of population growth, agricultural expansion, availability of resources, regional growth and infrastructure development as well as acculturation.This assessment aimedtoanalyzethe income structure, distributionand farmer household poverty in tidal swamp region. Survey had done in Saleh Mukti Village, Air Salek sub District, Banyuasin Regency, South Sumatera Province at October 2014. Using Disproportionated Stratified Random Sampling methodebased onrice farminglandownershipwiththreestrata, namely: narrow, medium andlarge strata. Each staraconsists of 14, 20 and 16 farmer households.The results showed that the average size of agriculture land ownership in narrow, medium and large strata were 1.03; 1.47 and 2.63 harespectively. The average income of farmer households in narrow, medium and large strata were Rp 23,360,675/year, Rp 28,973,970/year and Rp 36,158,060/year and about 18.21%, 42.40% and 34.62% get from the off-farm income. The distribution of those farmer household income per capita categorized on unequality with Gini coefficient 0.43.Household income of farmers per capita in narrow, medium and large strata were Rp 17,795/capita/year, Rp 30,625/capita/year and Rp 26,370/capita/year respectively. The percentageof poorhouseholdsin narrow, medium and largestrata were85.71%; 70% and75% respectively.Althoughpovertycan not becompletelyeliminated, butat leastthere areeffortsthat can be usedtoovercome it with community empowerment through: humanempowerment, businessempowermentandenvironment/infrastructure empowerment.